Method for treating vitamin k3 wastewater

CN122897488APending Publication Date: 2026-10-13SHANDONG SHANGRU HONGYI FINE CHEM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611331920.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]针对维生素K3废水预处理中难以在保证解毒深度的同时控制药剂与污泥代价的问题,本发明提供一种维生素K3废水处理方法

Benefits of technology

[0012]本发明的有益效果为:(1)以稀硫酸活化后置换沉积的方式在还原铁粉表面形成亚微米级弥散铜微阴极,经氮气保护烧结与铁碳骨架结合,所得填料的阴极位点密度与铁铜界面面积高于以等量铜粉机械混入制得的填料的相应值;铜的用量低于铁基多金属合金微电解填料中金属催化组分的常规配比,弥散分布提高了铜的利用效率。预处理出水B/C比由进水的0.11左右提高到0.32~0.39(较优条件下0.37~0.39),COD去除率达到43.8%~54.2%,高于同条件常规铁碳填料的33%左右;置换铜铁粉比例或铜负载量超出上述范围时,30天活性保持率降至71%~76%,上述范围可同时满足解毒效果与长周期稳定运行的要求。(2)处理过程中除曝气供氧外不投加氧化药剂,省去氧化药剂消耗;废水自带的亚硫酸氢盐持续还原阳极表面的三价铁钝化产物、维持电偶腐蚀电流,其自身转化率达到86%以上(较优条件下94%以上),还原性盐负荷在预处理段同步转化除去,减轻后续生化单元的耗氧冲击。(3)芯壳双层结构使置换铜铁粉集中于芯部,颗粒的机械强度主要由壳层提供并保护芯部电偶界面,填料连续运行30天的活性保持率不低于93%。(4)烧结中段的水蒸气活化在炭组分上形成孔道,改善废水与芯部电偶界面的传质;高温段温度控制在880~950℃、低于铜的熔点,保持弥散铜微阴极的分布,填料单颗粒抗压强度保持在180N以上,兼顾反应活性与机械强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to wastewater treatment technical field, specifically to a kind of vitamin K3 wastewater treatment method.Reduced iron powder is activated by dilute sulfuric acid, then copper is deposited by copper sulfate solution, and copper loading is 1%~3% of the mass of iron powder, to obtain replacement copper iron powder;Mixed with reduced iron powder, activated carbon powder, sodium bentonite and ammonium bicarbonate as dry mixture, replacement copper iron powder accounts for 10%~30% of the total iron mass of dry mixture;Wet rolling into core granules, after shell layer cloth coating, nitrogen protection sintering, 750~850 ℃ water vapor activation, 880~950 ℃ heat preservation, to obtain core-shell double-layer micro-electrolysis filler;Filler is loaded in aeration reactor, vitamin K3 wastewater containing bisulfite is introduced after adjusting pH to 4.0~5.5, aeration reaction is 2~3h, no oxidizing reagent is added except aeration oxygen supply, effluent is neutralized and precipitated.Wastewater-borne bisulfite maintains the anode activity of filler, and the B / C ratio of pretreated effluent reaches 0.32~0.39.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of industrial wastewater treatment technology, specifically relating to a method for treating vitamin K3 wastewater. Background Technology

[0002] Vitamin K3 is mainly produced by liquid-phase oxidation of 2-methylnaphthalenechromium salt to 2-methyl-1,4-naphthoquinone, followed by addition crystallization with sodium bisulfite. The mother liquor and washing water discharged during production contain 2-methyl-1,4-naphthoquinone and its sulfonated and addition derivatives, as well as naphthoquinone organic matter and high concentrations of salt. It has high chemical oxygen demand, dark color, and poor biodegradability. It needs to be effectively pretreated to improve its biodegradability before it can enter the biochemical treatment system.

[0003] Patent CN103613228B discloses a method for treating vitamin K3 production wastewater. After flocculation and slag removal, the wastewater is oxidized at 100-360℃ under oxygen pressure, followed by adsorption, decolorization, and deodorization. The treatment effect is good, but it requires a high-pressure reactor and an oxygen source, resulting in high equipment investment and energy consumption. Iron-carbon micro-electrolysis is a commonly used pretreatment method for recalcitrant wastewater, improving its biodegradability through galvanic cell reaction and chain scission. Patent CN109911992B discloses an iron-based multi-metal alloy micro-electrolysis packing material. Iron powder and copper powder, along with other metal catalytic components, are ball-milled and alloyed at a mass ratio of 40-60:7-17 (the metal catalytic components account for approximately 10%-30% of the alloy powder), then mixed with carbon and clay and granulated. The mixture is then sintered at 1150-1200℃ in an oxygen-deficient environment. This method has shown good results in treating dyeing and printing wastewater. Patent CN110643981A discloses a method for preparing bimetallic microelectrolysis materials by depositing copper on an iron-based surface using complexation displacement plating. The resulting material is then dried at a temperature not exceeding 80°C and used directly.

[0004] When the aforementioned materials are used for high-salt, high-concentration naphthoquinone wastewater such as vitamin K3 wastewater, the detoxification depth relying solely on the reduction effect of micro-electrolysis is limited. In engineering practice, it is often necessary to combine them with external oxidizing agents for enhancement, which increases the cost of the agents and the amount of iron-containing sludge. Furthermore, powdered bimetallic materials are easily lost with water during continuous operation, and the activity decline of conventional packing materials is also significant over long-term operation. How to improve the detoxification depth of this type of wastewater pretreatment without increasing the dosage of oxidizing agents, while maintaining the long-term activity of the packing materials, remains a problem to be solved in this field. Summary of the Invention

[0005] To address the problem of controlling the cost of reagents and sludge while ensuring the depth of detoxification in the pretreatment of vitamin K3 wastewater, this invention provides a method for treating vitamin K3 wastewater.

[0006] The present invention adopts the following technical solution: a method for treating vitamin K3 wastewater, comprising the following steps: (1) preparation of replacement copper-iron powder: the reduced iron powder is stirred and activated in dilute sulfuric acid with a mass fraction of 2%~4%, the acid is poured off and copper sulfate aqueous solution is added, stirred and replaced until the blue liquid phase disappears, washed, and dried in oxygen-free condition to obtain replacement copper-iron powder; the copper loading of the replacement deposit is 1%~3% of the mass of the reduced iron powder; (2) preparation of core material: the replacement copper-iron powder, reduced iron powder, activated carbon powder, sodium bentonite and ammonium bicarbonate are mixed evenly to obtain dry mixture; the binder aqueous solution is added to the dry mixture to wet it to obtain core material; the replacement copper-iron powder accounts for 10%~30% of the total mass of replacement copper-iron powder and reduced iron powder in the dry mixture, and the copper deposited accounts for 0.2%~0.65% of the total mass of replacement copper-iron powder and reduced iron powder in the dry mixture; (3) granulation of core shell: The core material is rolled into core particles, and then the core particles are covered with a shell material composed of sodium bentonite, reduced iron powder and activated carbon powder to obtain a core-shell double-layer green body; (4) Drying and sintering: After drying the green body, the temperature is raised under nitrogen protection, and steam is introduced at 750~850℃ to activate the carbon components. After stopping the steam, the temperature is raised to 880~950℃ for heat preservation and sintering. After cooling, a core-shell double-layer micro-electrolysis packing is obtained; (5) Micro-electrolysis treatment: The core-shell double-layer micro-electrolysis packing is filled into an aeration reactor. Vitamin K3 wastewater with a total amount of bisulfite not less than 500mg / L as calculated by bisulfite and determined by indirect iodometric method is introduced after adjusting the pH to 4.0~5.5. The aeration reaction is carried out for 2~3 hours. No oxidizing agent is added during the treatment process except for aeration and oxygen supply; (6) The pH of the micro-electrolysis effluent is adjusted to 8.0~8.5 with alkali, and the precipitate is separated into solid and liquid.

[0007] Further, in step (1), the stirring and activation time is 3-5 min, the copper sulfate aqueous solution is a 5%-8% (w / w) copper sulfate pentahydrate aqueous solution, and the displacement time is 15-30 min; the drying temperature of the displacement copper-iron powder is 60-80℃. Further, in step (2), by mass percentage, the total mass percentage of the displacement copper-iron powder and reduced iron powder in the dry mixture is 58%-64%, activated carbon powder is 18%-22%, sodium bentonite is 12%-15%, and ammonium bicarbonate is 3%-5%, and the sum of the mass percentages of the above components is 100%.

[0008] Further, in step (3), the amount of shell material is 10%~15% of the dry mixture mass. Further, in the shell material, by mass percentage, sodium bentonite is 45%~50%, reduced iron powder is 32%~38%, activated carbon powder is 15%~20%, and the sum of the mass percentages of the above components is 100%. Further, in step (3), the particle size of the core particles is 6~10mm. Further, in step (4), the green body is first air-dried and then dried at 100~110℃ for 4~6h, the heating rate is 5~8℃ / min, the steam flow rate is 0.5~1mL / (min·kg green body) based on liquid water, the activation time is 30~60min, and the holding time at 880~950℃ is 1~2h. Furthermore, in step (5), the packing volume is 40% to 60% of the effective volume of the aeration reactor, and the aeration intensity is 3:1 to 5:1, calculated as the ratio of the volume of air introduced per hour to the volume of wastewater to be treated; in step (6), the sedimentation time is 30 to 60 minutes.

[0009] Furthermore, the vitamin K3 wastewater is a mixture of addition crystallization mother liquor and washing water from vitamin K3 production, with a CODcr of 8000~12000 mg / L and a total bisulfite content of 500~1500 mg / L as calculated by bisulfite and determined by indirect iodometric titration.

[0010] The technical problem and solution of this invention are as follows: The mother liquor wastewater from vitamin K3 production contains naphthoquinone toxic substances and high concentrations of salt, exhibiting low biodegradability. Micro-electrolysis pretreatment typically requires external oxidizing agents to achieve sufficient detoxification depth. However, this agent addition incurs costs and creates iron-containing sludge, making it difficult to control the costs of agents and sludge while ensuring sufficient detoxification depth. This method does not rely on external oxidizing agents: it enhances galvanic reduction by replacing the deposited dispersed copper microcathode. The bisulfite naturally present in the wastewater continuously reduces the trivalent iron passivation products on the anode surface, maintaining the galvanic corrosion current. Simultaneously, the reducing salt load is converted and removed during detoxification.

[0011] The present invention also provides a micro-electrolysis filler, which is prepared by steps (1) to (4) of the above method. The filler has a core-shell double-layer structure. The core is an electrocouple reaction zone formed by replacing copper-iron powder and iron-carbon skeleton with nitrogen protection sintering. The mechanical strength of the particles is mainly provided by the shell layer. Its single particle compressive strength is above 180N, and the activity retention rate is not less than 93% after 30 days of continuous operation.

[0012] The beneficial effects of this invention are as follows: (1) Submicron-level dispersed copper microcathodes are formed on the surface of reduced iron powder by displacement deposition after activation with dilute sulfuric acid. After nitrogen protection sintering, the cathode site density and iron-copper interface area of ​​the resulting filler are higher than the corresponding values ​​of the filler prepared by mechanically mixing in an equal amount of copper powder. The amount of copper used is lower than the conventional ratio of metal catalytic components in iron-based multimetal alloy microelectrolysis fillers, and the dispersed distribution improves the utilization efficiency of copper. The B / C ratio of the pretreated effluent increases from about 0.11 to 0.32~0.39 (0.37~0.39 under better conditions), and the COD removal rate reaches 43.8%~54.2%, which is higher than about 33% of conventional iron-carbon fillers under the same conditions. When the ratio of copper-iron powder replacement or the copper loading exceeds the above range, the activity retention rate drops to 71%~76% after 30 days. The above range can simultaneously meet the requirements of detoxification effect and long-term stable operation. (2) No oxidizing agent is added during the treatment process except for aeration and oxygen supply, saving the consumption of oxidizing agent; the bisulfite in the wastewater continuously reduces the trivalent iron passivation products on the anode surface and maintains the galvanic corrosion current, and its own conversion rate reaches more than 86% (more than 94% under better conditions). The reducing salt load is converted and removed in the pretreatment section, reducing the oxygen consumption impact of the subsequent biochemical unit. (3) The core and shell double-layer structure concentrates the replacement copper iron powder in the core. The mechanical strength of the particles is mainly provided by the shell layer and protects the core galvanic interface. The activity retention rate of the packing is not less than 93% after 30 days of continuous operation. (4) The water vapor activation in the sintering section forms channels on the carbon components, improving the mass transfer between the wastewater and the core galvanic interface; the temperature in the high-temperature section is controlled at 880~950℃, which is lower than the melting point of copper, maintaining the distribution of dispersed copper micro cathodes. The compressive strength of a single packing particle is maintained above 180N, taking into account both reaction activity and mechanical strength. Detailed Implementation

[0013] The present invention will be further described below with reference to the preparation examples, embodiments, and comparative examples. The reduced iron powder used in the preparation examples, embodiments, and comparative examples was sourced from Shanghai Guanjin Powder Materials Co., Ltd., brand name CNPC-Fe, with a particle size of 100-200 mesh; the activated carbon powder was sourced from Sichuan Longbang Water Purification Materials Co., Ltd., brand name LB-707, with a particle size of 200-325 mesh and an iodine value of not less than 800 mg / g; the sodium bentonite was sourced from Zhejiang Fenghong New Materials Co., Ltd., and was sodium bentonite for granulation; the ammonium bicarbonate was sourced from Weifang Dongpu Industrial Co., Ltd., and was an industrial-grade product; the copper sulfate pentahydrate was an analytical grade product supplied by Leyan Reagent; the copper powder used in the comparative examples was electrolytic copper powder with a particle size of approximately 200 mesh. Sulfuric acid, sodium hydroxide, and sodium carboxymethyl cellulose were all conventional commercially available chemicals.

[0014] Preparation Example 1: Displacement of Copper-Iron Powder A

[0015] Add 5000g of reduced iron powder to 10000g of 3% dilute sulfuric acid and stir for 4min to remove the surface oxide film. Pour off the acid solution. Immediately add 6550g of 6% copper sulfate pentahydrate aqueous solution (containing 393g of copper sulfate pentahydrate) and stir at 25℃ for 20min until the blue color of the liquid phase disappears. Pour off the supernatant and wash three times with water until the washing solution is colorless. Dry under a nitrogen stream at 70℃ to obtain 4510g of replaced copper iron powder. Its copper loading is 2% of the mass of the reduced iron powder, and the copper accounts for 2% of the mass fraction of the replaced copper iron powder. This is denoted as replaced copper iron powder A.

[0016] Preparation Example 2: Displacement of Copper-Iron Powder B

[0017] Add 500g of reduced iron powder to 1000g of 3% dilute sulfuric acid and stir for 4 minutes to activate. Pour off the acid solution. Immediately add 327g of 6% copper sulfate pentahydrate aqueous solution (containing 19.6g of copper sulfate pentahydrate) and stir at 25℃ for 20 minutes until the blue color of the liquid phase disappears. Pour off the supernatant and wash with water 3 times until the washing liquid is colorless. Dry under a nitrogen stream at 70℃ to obtain 451g of replaced copper iron powder. Its copper loading is 1% of the mass of reduced iron powder, and the copper accounts for 1% of the mass fraction of the replaced copper iron powder. This is denoted as replaced copper iron powder B.

[0018] Preparation Example 3: Replacement of Copper-Iron Powder C

[0019] Add 500g of reduced iron powder to 1000g of 3% dilute sulfuric acid and stir for 4 minutes to activate. Pour off the acid solution. Immediately add 982g of 6% copper sulfate pentahydrate aqueous solution (containing 58.9g of copper sulfate pentahydrate) and stir at 25℃ for 20 minutes until the blue color of the liquid phase disappears. Pour off the supernatant and wash with water 3 times until the washing liquid is colorless. Dry under a nitrogen stream at 70℃ to obtain 452g of replaced copper iron powder. Its copper loading is 3% of the mass of the reduced iron powder, and the copper accounts for 3% of the mass fraction of the replaced copper iron powder. This is denoted as replaced copper iron powder C.

[0020] Preparation Example 4: Drying and Nitrogen-Protected Sintering Method for Core-Shell Double-Layer Green Green

[0021] The green billets were air-dried in a cool place for 24 hours, and then dried at 105℃ for 5 hours. The dried green billets were then loaded into a sintering furnace and heated at 6℃ / min under nitrogen protection. When the temperature reached 800℃, steam was introduced at 0.75mL / min (based on liquid water) per kilogram of green billet, and the furnace was kept at this temperature for 45 minutes for activation. After the steam was stopped, the temperature was continued to rise to 915℃ and kept at this temperature for 1.5 hours. The furnace was then cooled to room temperature before being discharged.

[0022] Example 1:

[0023] 415g of copper-iron powder A, 1659g of reduced iron powder, 680g of activated carbon powder, 459g of sodium bentonite and 136g of ammonium bicarbonate obtained in Preparation Example 1 were dry-mixed evenly in a mixer. 255g of 2% sodium carboxymethyl cellulose aqueous solution was sprayed in as a binding aid, and mixing continued until the material was uniformly wetted.

[0024] The mixture is fed into a disc granulator and sprayed with an appropriate amount of water to roll it into core pellets with a diameter of 8mm. Separately, 192g of sodium bentonite, 145g of reduced iron powder and 71g of activated carbon powder are mixed evenly as shell material and then applied to the rolling core pellets to cover them. The amount of shell material is 12.2% of the dry mixture mass, resulting in a core-shell double-layer green body.

[0025] The green blank was dried and sintered according to the method of Preparation Example 4 to obtain 3519g of core-shell double-layer micro-electrolysis filler.

[0026] Example 2:

[0027] 208g of copper-iron powder A, 1866g of reduced iron powder, 680g of activated carbon powder, 459g of sodium bentonite and 136g of ammonium bicarbonate obtained in Preparation Example 1 were dry-mixed evenly in a mixer. 255g of sodium carboxymethyl cellulose aqueous solution with a mass fraction of 2% was sprayed in as a binding aid, and the mixture was continued until the material was uniformly wetted.

[0028] The mixture is fed into a disc granulator and sprayed with an appropriate amount of water to roll it into core pellets with a diameter of 8mm. Separately, 192g of sodium bentonite, 145g of reduced iron powder and 71g of activated carbon powder are mixed evenly as shell material and then applied to the rolling core pellets to cover them. The amount of shell material is 12.2% of the dry mixture mass, resulting in a core-shell double-layer green body.

[0029] The green blank was dried and sintered according to the method of Preparation Example 4 to obtain 3514g of core-shell double-layer micro-electrolysis filler.

[0030] Example 3:

[0031] 622g of copper-iron powder A, 1452g of reduced iron powder, 680g of activated carbon powder, 459g of sodium bentonite and 136g of ammonium bicarbonate obtained in Preparation Example 1 were dry-mixed evenly in a mixer. 255g of sodium carboxymethyl cellulose aqueous solution with a mass fraction of 2% was sprayed in as a binding aid, and the mixture was continued until the material was evenly wetted.

[0032] The mixture is fed into a disc granulator and sprayed with an appropriate amount of water to roll it into core pellets with a diameter of 8mm. Separately, 192g of sodium bentonite, 145g of reduced iron powder and 71g of activated carbon powder are mixed evenly as shell material and then applied to the rolling core pellets to cover them. The amount of shell material is 12.2% of the dry mixture mass, resulting in a core-shell double-layer green body.

[0033] The green blank was dried and sintered according to the method of Preparation Example 4 to obtain 3512g of core-shell double-layer micro-electrolysis filler.

[0034] Example 4:

[0035] 415g of copper-iron powder B obtained in Preparation Example 2, 1659g of reduced iron powder, 680g of activated carbon powder, 459g of sodium bentonite and 136g of ammonium bicarbonate were dry-mixed evenly in a mixer, and 255g of 2% sodium carboxymethyl cellulose aqueous solution was sprayed in as a binding aid, and the mixture was continued until the material was evenly wetted.

[0036] The mixture is fed into a disc granulator and sprayed with an appropriate amount of water to roll it into core pellets with a diameter of 8mm. Separately, 192g of sodium bentonite, 145g of reduced iron powder and 71g of activated carbon powder are mixed evenly as shell material and then applied to the rolling core pellets to cover them. The amount of shell material is 12.2% of the dry mixture mass, resulting in a core-shell double-layer green body.

[0037] The green blank was dried and sintered according to the method of Preparation Example 4 to obtain 3516g of core-shell double-layer micro-electrolysis filler.

[0038] Example 5:

[0039] The copper-iron powder C 415g, reduced iron powder 1659g, activated carbon powder 680g, sodium bentonite 459g and ammonium bicarbonate 136g obtained in Preparation Example 3 were dry-mixed evenly in a mixer. 255g of sodium carboxymethyl cellulose aqueous solution with a mass fraction of 2% was sprayed in as a binding aid, and the mixture was continued until the material was evenly wetted.

[0040] The mixture is fed into a disc granulator and sprayed with an appropriate amount of water to roll it into core pellets with a diameter of 8mm. Separately, 192g of sodium bentonite, 145g of reduced iron powder and 71g of activated carbon powder are mixed evenly as shell material and then applied to the rolling core pellets to cover them. The amount of shell material is 12.2% of the dry mixture mass, resulting in a core-shell double-layer green body.

[0041] The green blank was dried and sintered according to the method of Preparation Example 4 to obtain 3521g of core-shell double-layer micro-electrolysis filler.

[0042] Comparative Example 1:

[0043] Except for replacing the copper-iron powder A obtained in Preparation Example 1 with an equal mass of ball-milled mixed powder, the other raw materials, amounts, and preparation conditions were the same as in Example 1, yielding 3515g of micro-electrolysis filler. The ball-milled mixed powder was obtained by ball-milling 406.7g of reduced iron powder and 8.3g of copper powder for 2 hours under nitrogen protection.

[0044] Comparative Example 2:

[0045] Except for not adding copper-iron powder A and changing the amount of reduced iron powder in the dry mixture to 2074g, the other raw materials, amounts and preparation conditions were the same as in Example 1, and 3518g of micro-electrolysis filler was obtained.

[0046] Comparative Example 3:

[0047] Except for not applying the shell layer and directly sintering the core particles after drying, the other raw materials, dosages, and preparation conditions were the same as in Example 1, resulting in 3137g of shell-less micro-electrolysis filler.

[0048] Comparative Example 4:

[0049] Except for the fact that no water vapor was introduced during the drying and sintering process according to the method of Preparation Example 4, and that the other heating and holding procedures remained unchanged, the other raw materials, amounts and preparation conditions were the same as in Example 1, and 3568g of micro-electrolysis filler was obtained.

[0050] Comparative Example 5:

[0051] A filler without replacement copper and iron powder was prepared using the same method as in Comparative Example 2. During performance testing, 3000g of this filler was used, with 11.8g of replacement copper and iron powder A obtained in Preparation Example 1 added to each batch along with the influent, totaling 354g for 30 batches. The remaining treatment conditions were the same as described in the performance test.

[0052] Comparative Example 6:

[0053] The packing material was prepared separately using the same method as in Example 1. For performance testing, 4L of the treated wastewater was taken from each batch, and the pH was adjusted to 1.5 with sulfuric acid. The wastewater was then stripped of bisulfite in a container with a reflux condenser at 80°C with nitrogen gas at a rate of 10L / min for 30 minutes. Bisulfite was not detected in the wastewater after stripping, as determined by indirect iodometric titration. After stripping, deionized water was added to the original volume, and the pH was adjusted using a 30% sodium hydroxide solution. The wastewater was then cooled to room temperature, and the CODcr was measured to be 9940 mg / L. All other treatment conditions were the same as described in the performance test.

[0054] Comparative Example 7:

[0055] Except for changing the amount of copper-iron powder A in the dry mixture to 830g and the amount of reduced iron powder to 1244g, the other raw materials, amounts and preparation conditions were the same as in Example 1, and 3513g of micro-electrolysis filler was obtained.

[0056] Comparative Example 8:

[0057] Except for changing the amount of copper-iron powder A in the dry mixture to 104g and the amount of reduced iron powder to 1970g, the other raw materials, amounts and preparation conditions are the same as in Example 1, and 3520g of micro-electrolysis filler is obtained.

[0058] Comparative Example 9:

[0059] Except for replacing the copper-iron powder A with copper-iron powder prepared by using 98.2g of copper sulfate pentahydrate per 500g of reduced iron powder according to the method of Preparation Example 1 (the copper loading is 5% of the mass of reduced iron powder, and the copper accounts for 5% of the mass fraction of the copper-iron powder), the other raw materials, dosages and preparation conditions are the same as in Example 1, and 3516g of micro-electrolysis filler is obtained.

[0060] Comparative Example 10:

[0061] Except for replacing the copper-iron powder A with copper-iron powder prepared by using 9.8g of copper sulfate pentahydrate per 500g of reduced iron powder according to the method of Preparation Example 1 (the copper loading is 0.5% of the mass of reduced iron powder, and the copper accounts for 0.5% of the mass fraction of the copper-iron powder), the other raw materials, dosages and preparation conditions are the same as in Example 1, and 3517g of micro-electrolysis filler is obtained.

[0062] Comparative Example 11:

[0063] Except for changing the high-temperature section holding temperature from 915℃ to 1180℃ during drying and sintering according to the method of Preparation Example 4, and keeping the rest of the procedure unchanged, the other raw materials, amounts and preparation conditions are the same as in Example 1, and 3462g of micro-electrolysis filler is obtained.

[0064] Performance testing:

[0065] The wastewater to be treated consisted of a mixture of mother liquor from the addition crystallization of vitamin K3 production and washing water. Its CODcr was 10100 mg / L, BOD5 was 1150 mg / L, bisulfite was 960 mg / L (calculated as bisulfite, the total amount determined by indirect iodometric titration, including free and dissociable addition states, the same below), salt content (calculated as sodium sulfate) was approximately 6.8%, chloride ion concentration was 1820 mg / L as determined by GB / T11896-1989 "Determination of Chloride in Water - Silver Nitrate Titration Method" (the water sample was first oxidized with a small amount of hydrogen peroxide to eliminate the interference of sulfite on the titration), and pH was 3.2 as determined by HJ 1147-2020 "Determination of pH Value in Water - Electrode Method".

[0066] 3000g of the packing material obtained in each embodiment and comparative example was packed into an aeration reaction column. The effective volume of the reaction zone inside the column was 6L, the packing material volume was about 3L, and the packing volume fraction was 50%. Comparative example 5 was packed and added in the manner described therein. 4L of wastewater to be treated was taken for each batch, and the pH was adjusted to 4.8 with a 30% sodium hydroxide solution before being added. The mixture was aerated at room temperature at a ratio of air volume to wastewater volume of 4:1 (i.e., 16L / h) for 2.5h. No oxidizing agents were added during the treatment process except for aeration and oxygen supply. The pH of the effluent was adjusted to 8.2 with a 30% sodium hydroxide solution, and the mixture was allowed to settle for 45min. The supernatant was then measured. Continuous operation was tested by treating one batch per day in the same manner for 30 consecutive days. The packing material was preserved by immersion in the effluent for the remaining time. The data listed in Table 1 are the measured values ​​of the effluent on the first day of continuous operation. CODCr was measured on the effluent on the 10th, 20th, and 30th days.

[0067] The CODcr of the effluent was determined according to HJ 828-2017 "Determination of Chemical Oxygen Demand in Water - Dichromate Method". High-concentration samples were diluted before testing. The BOD5 of the effluent was determined according to HJ 505-2009 "Determination of Five-Day Biochemical Oxygen Demand (BOD5) in Water - Dilution and Inoculation Method". The bisulfite of the effluent was determined using the supernatant after settling as the test solution, referring to the indirect iodometric method in "Methods for Monitoring and Analysis of Water and Wastewater" (Fourth Edition), with a detection limit of 5 mg / L. The single-particle compressive strength was tested using filler particles. Ten particles were placed one by one between the plates of an electronic universal testing machine and pressurized at 5 mm / min until crushed. The crushing load was recorded and the arithmetic mean was taken. Except for the single-particle compressive strength, each item was measured in parallel three times for each sample, and the arithmetic mean was taken. The effluent B / C ratio was calculated as the ratio of effluent BOD5 to effluent CODCr. The COD removal rate was calculated based on the influent and effluent CODCr, with Comparative Example 6 using a CODCr of 9940 mg / L for the stripped wastewater. The bisulfite conversion rate was calculated based on the influent and effluent bisulfite levels; the 30-day activity retention rate was calculated as the ratio of the COD removal rate on day 30 to the COD removal rate on day 1. Comparative Example 6 used a packing material prepared separately using the same method as in Example 1, and its packing strength is shown in Example 1. The bisulfite conversion rate is not applicable. Copper loading, the mass fraction of copper in the replaced copper-iron powder, and the total copper percentage were all calculated based on the feed metering. The results are shown in Tables 1 to 3.

[0068] Table 1. Main performance of wastewater treatment in each embodiment and comparative example.

[0069]

[0070] Table 2 Bisulfite Conversion and Packing Strength

[0071]

[0072] Table 3 Continuous Operation Assessment Results

[0073]

[0074] Results Analysis

[0075] As shown in Table 1, the influent B / C ratio was approximately 0.11, while the effluent B / C ratios for Examples 1 to 5 ranged from 0.32 to 0.39. Comparative Example 2, which did not contain the replacement copper and iron powder, had an effluent B / C ratio of 0.24 and a COD removal rate of 33.1%, while Example 1 achieved 0.37 and 51.0%, respectively. This indicates that the introduction of replacement copper and iron powder into the dry mix accelerated the galvanic corrosion and reduction conversion of the packing material by the dispersed copper microcathode, thereby improving the biodegradability of the effluent.

[0076] Comparative Example 1 replaced the copper-iron powder with a ball-milled mixed powder of the same amount of copper. The B / C ratio of the effluent was 0.29, and the COD removal rate was 37.9%, both significantly lower than that of Example 1. This indicates that under the condition of the same copper content of 8.3g, displacement deposition forms submicron-sized dispersed copper on the surface of each iron powder particle. The cathode site density and iron-copper interface area of ​​the resulting filler are higher than the corresponding values ​​of the filler prepared by ball milling and mixing copper powder. Copper must be introduced by displacement deposition to obtain a sufficient galvanic reaction rate.

[0077] Comparative Example 6 used the same method as Example 1 to prepare the packing material, with the same batch of wastewater after stripping to remove bisulfite as the treated wastewater. Based on a CODcr of 9940 mg / L in the stripped wastewater, the COD removal rate was 41.6%, and the effluent B / C ratio was 0.31, which were 9.4 percentage points and 0.06 lower than those in Example 1, respectively. Under conditions where no oxidizing agents were added except for aeration and oxygen supply, the presence or absence of inherent bisulfite directly affected the detoxification depth. This may be related to the fact that bisulfite continuously reduces the trivalent iron passivation products on the anode surface to soluble ferrous iron, maintaining the effective anode surface area and galvanic corrosion current.

[0078] As shown in Table 2, the bisulfite conversion rate in Example 1 was 94.8%, while that in Comparative Example 2 was 50.5%. This indicates that the copper-containing packing accelerated the conversion of bisulfite into higher-valence sulfur-containing components. This portion of the reducing load was converted and removed in the pretreatment stage, reducing the oxygen consumption impact on subsequent biochemical units.

[0079] The COD removal rate of Comparative Example 3 without a shell was 50.5% on the first day, which was close to that of Example 1, but the compressive strength of a single particle was only 122 N. As shown in Table 3, its 30-day activity retention rate was 71.8%, which was lower than 93.8% of Example 1. The mechanical strength of the particles is mainly provided by the shell. Without a shell, the highly active core surface is directly exposed, and corrosion products and flocs accumulate on the particle surface more quickly. Insufficient strength also causes the particles to break and generate dust during loading and operation, and the activity decreases accordingly.

[0080] In Comparative Example 4, no steam was introduced during sintering, resulting in an effluent B / C ratio of 0.32 and a bisulfite conversion rate of 90.1%, both lower than in Example 1. The compressive strength of a single packing particle in Comparative Example 4 was 200 N, higher than in all examples. This indicates that steam activation of the pores formed on the carbon components improved the contact and mass transfer between the wastewater and the core electrode interface, while slightly reducing the packing strength. Within the steam flow rate and activation time range of this invention, the packing's reactivity and mechanical strength both meet the usage requirements.

[0081] When replacement copper-iron powder was added in powder form with each batch of influent after the packing was sintered (Comparative Example 5), the COD removal rate on the first day was 47.5%, which was not much different from Example 1. The added powder was in a suspended state and fully contacted the wastewater, and the utilization rate per unit mass was higher than that of the packing material packed in the bed. Therefore, a small amount of powder could achieve a comparable effect on the first day. However, its 30-day activity retention rate was only 54.8%. The fine powder portion of the copper-iron powder was carried out with the drainage, and the portion retained in the column accumulated batch by batch in the form of hydrated iron oxide, coating the surface of the packing material and blocking the flow channel. Even if new powder was added with each batch, it was impossible to maintain the treatment effect on the first day. Replacement copper-iron powder can only maintain its activity during long-term operation after being mixed with dry materials before granulation and sintered under nitrogen protection and combined with the skeleton.

[0082] When the proportion of copper-iron powder in the dry mixture was increased from 10% (Example 2) to 30% (Example 3), the effluent B / C ratio increased from 0.34 to 0.39. Comparative Example 8 reduced this proportion to 5%, and the effluent B / C ratio was 0.26, showing only a limited improvement compared to Comparative Example 2. Comparative Example 7 increased this proportion to 40%, but the effluent B / C ratio actually decreased to 0.32, and its effluent bisulfite concentration dropped to around 30 mg / L, indicating near-complete conversion. However, as shown in Table 3, its 30-day activity retention rate was only 71.0%. When this proportion is too high, the number of short-circuit couples formed by the contact between the copper-iron powder particles increases, hydrogen evolution and diversion intensifies, and localized alkalization in the cathode area causes iron hydroxide to accumulate on the particle surface, covering the active surface. This reduces the effective current for reducing organic pollutants, and significantly accelerates long-term activity decay.

[0083] The effect of copper loading is similar to that of the proportion of copper-iron powder in the replacement process: the effluent B / C ratios of Example 4 (1%) and Example 5 (3%) were 0.32 and 0.37, respectively; the copper loading of Comparative Example 10 was 0.5%, and the effluent B / C ratio was 0.24, comparable to Comparative Example 2 without copper; the copper loading of Comparative Example 9 was 5%, and the effluent B / C ratio was 0.32, with a bisulfite conversion rate of 93.2% and a 30-day activity retention rate of 76.2%, significantly lower than that of Example 1. Insufficient copper leads to an insufficient number of microcathodes; excessive copper reduces the effective anode area by covering the iron surface, increases hydrogen evolution diversion, and no longer improves the initial performance. During long-term operation, uneven dissolution of the iron matrix at the copper layer coverage and accelerated deterioration of the particle surface structure occur. Based on the total copper percentage, the copper deposited in Examples 1 to 5 accounted for 0.40%, 0.20%, 0.60%, 0.20%, and 0.60% of the total mass of replaced copper iron powder and reduced iron powder in the dry mixture, respectively. The corresponding values ​​for Comparative Examples 7 to 10 were 0.80%, 0.10%, 1.00%, and 0.10%, respectively. In this invention, the amount of copper used is far lower than the conventional ratio of metal catalytic components in iron-based multimetal alloy micro-electrolysis fillers, and the dispersed distribution improves the utilization efficiency of copper.

[0084] Comparative Example 11 increased the high-temperature section holding temperature from 915℃ to 1180℃, exceeding the melting point of copper. The resulting filler had a water effluent B / C ratio of 0.29, a bisulfite conversion rate of 75.0%, and a single-particle compressive strength of 215N. This indicates that when sintering above the copper melting point, the surface-dispersed copper melts and aggregates, the microcathode distribution is lost, the bentonite tends to vitrify, making the pores denser, and the reactivity significantly decreases. Controlling the high-temperature section at 880~950℃ is necessary to maintain the dispersed copper microcathode and pore structure.

[0085] During 30 days of continuous operation, the CODcr of the effluent from Example 1 slowly increased from 4950 mg / L to 5270 mg / L, with a 30-day activity retention rate of 93.8%, higher than that of Comparative Example 1 (77.5%) and Comparative Example 2 (69.5%). These results indicate that this method, by enhancing galvanic reduction with a dispersed copper microcathode and maintaining anolyte activity using the bisulfite naturally present in the wastewater, achieves deep detoxification without the addition of oxidizing agents, except for aeration and oxygen supply. The pretreated effluent achieved a B / C ratio of 0.32–0.39, creating conditions for subsequent biological treatment.

Claims

1. A method for treating vitamin K3 wastewater, characterized in that, Includes the following steps: (1) Preparation of copper-iron powder by displacement: Reduced iron powder is activated by stirring in dilute sulfuric acid with a mass fraction of 2%~4%, the acid solution is poured off, copper sulfate aqueous solution is added, and the mixture is stirred until the blue color of the liquid phase disappears. The mixture is washed, dried in the absence of oxygen, and copper-iron powder by displacement is obtained. The copper loading of the displacement deposit is 1%~3% of the mass of the reduced iron powder. (2) Core material preparation: The copper-iron powder, reduced iron powder, activated carbon powder, sodium bentonite and ammonium bicarbonate are mixed evenly to obtain a dry mixture; an aqueous solution of binder is added to the dry mixture to wet it to obtain the core material; the copper-iron powder accounts for 10% to 30% of the total mass of the copper-iron powder and reduced iron powder in the dry mixture, and the copper deposited accounts for 0.2% to 0.65% of the total mass of the copper-iron powder and reduced iron powder in the dry mixture; (3) Core and shell granulation: The core material is rolled into core particles, and then the core particles are covered with a shell material composed of sodium bentonite, reduced iron powder and activated carbon powder to obtain a double-layer green body with core and shell. (4) Drying and sintering: After drying the green body, the temperature is raised under nitrogen protection. Steam is introduced at 750~850℃ to activate the carbon components. After stopping the steam supply, the temperature is raised to 880~950℃ and sintered. After cooling, a core-shell double-layer micro-electrolysis filler is obtained. (5) Micro-electrolysis treatment: The core-shell double-layer micro-electrolysis packing is filled into the aeration reactor. Vitamin K3 wastewater with a total amount of bisulfite (calculated as bisulfite and determined by indirect iodometric method) of not less than 500 mg / L is introduced after adjusting the pH to 4.0~5.

5. The aeration reaction is carried out for 2~3 hours. No oxidizing agents are added during the treatment process except for aeration and oxygen supply. (6) Adjust the pH of the micro-electrolysis effluent to 8.0~8.5 with alkali, precipitate, and separate solids and liquids.

2. The vitamin K3 wastewater treatment method according to claim 1, characterized in that, In step (1), the stirring activation time is 3-5 min, the copper sulfate aqueous solution is a copper sulfate pentahydrate aqueous solution with a mass fraction of 5%-8%, and the replacement time is 15-30 min.

3. The vitamin K3 wastewater treatment method according to claim 1, characterized in that, In step (2), by mass percentage, the dry mixture contains 58% to 64% copper-iron powder and reduced iron powder, 18% to 22% activated carbon powder, 12% to 15% sodium bentonite, and 3% to 5% ammonium bicarbonate, and the sum of the mass percentages of the above components is 100%.

4. The vitamin K3 wastewater treatment method according to claim 1, characterized in that, In step (3), the amount of shell material used is 10% to 15% of the mass of the dry mixture in step (2).

5. The vitamin K3 wastewater treatment method according to claim 1, characterized in that, In step (3), the shell material contains 45%~50% sodium bentonite, 32%~38% reduced iron powder, and 15%~20% activated carbon powder by mass percentage, and the sum of the mass percentages of the above components is 100%.

6. The vitamin K3 wastewater treatment method according to claim 1, characterized in that, In step (4), the heating rate is 5~8℃ / min, the steam flow rate is 0.5~1mL / (min·kg green body) based on liquid water, the steam activation time is 30~60min, and the holding time at 880~950℃ is 1~2h.

7. The vitamin K3 wastewater treatment method according to claim 1, characterized in that, In step (5), the filling volume of the core-shell double-layer micro-electrolysis packing is 40% to 60% of the effective volume of the aeration reactor, and the aeration intensity is calculated as the ratio of the volume of air introduced per hour to the volume of wastewater to be treated as 3:1 to 5:

1.

8. The vitamin K3 wastewater treatment method according to claim 1, characterized in that, The vitamin K3 wastewater is a mixture of addition crystallization mother liquor and washing water from vitamin K3 production. Its CODcr is 8000~12000 mg / L, and the total amount of bisulfite, calculated as bisulfite and determined by indirect iodometric titration, is 500~1500 mg / L.

9. A micro-electrolysis filler, characterized in that, It is prepared by steps (1) to (4) of the vitamin K3 wastewater treatment method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • A method for treating vitamin K3 production wastewater

    CN103613228B

  • Preparation method and application of iron-based multimetallic alloy microelectrolysis filler

    CN109911992B

  • Nano-micron combined iron-based bimetallic microelectrolysis material and preparation method thereof

    CN110643981A